Early-induced diabetic obese rat MACAPOS 2 - Joseph Ngakou Mukam; Clémence Mvongo; Sandrine Nkoubat; Gaëtan Olivier Fankem; Adamou Mfopa; Paul Aimé Noubissi; Michel Archange Fokam Tagne; René Kamgang; Jean-Louis Essame Oyono (BMC Endocrine Disorders, 2023)
Abstract Background Diabetes mellitus is a metabolic disease characterized by an abnormally high blood glucose level. Glucose intolerance and insulin resistance are two characteristics that promote the onset and development of type 2 diabetes. The aim of this study was to create a diabetic rat model from obese rat MACAPOS 2. Methods A group of rats was subjected to a high-fat diet (HFD) compared to a control group (NC) which received a normal diet. After 16 weeks of HFD, Lee index was calculated, obese rats were subjected to an oral glucose tolerance test (OGTT) and insulin tolerance test (ITT). One group of HFD rats (HFDZ) received streptozotocin 22.5 mg/kg (iv). One week later, weight gain, water and food intakes, urine volume and fasting blood glucose levels were evaluated. Animals were also subjected to glucose tolerance and insulin tolerance tests. Results After 16 weeks of HFD, rats became obese, glucose intolerant and resistant to insulin. The body weight of rats was significantly high (+ 26.23%) compared to normal rats, glycemia remained significantly high (+ 45.46%, P < 0.01) two hours after administration of glucose in high-fat diet rats, water intake and urine volume were comparable to those of NC. In HFD, the streptozotocin injected after one week (HFDZ), amplified glucose intolerance. During ITT, glycemia remained significantly (P < 0.01) high from 15 min; and did not vary during the 60 min of ITT. The fasting glycemia one week after streptozotocin injection was significantly high (288 mg/dL) compared to HFD (114 mg/dL), associated whit a significant (P < 0.01) increase in water intake and 24 h urine volume. Conclusion These results showed that MACAPOS 2 associated with a low dose of streptozotocin (22.5 mg/dL) early leads to the diabetes in obese albinos Wistar rats and could be a real model to study the type 2 diabetes mellitus.